Managerial and financial barriers to the net-zero transition - Ralph De Haas; Ralf Martin; Mirabelle Muûls; Helena Schweiger (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2021)
We use data on 11,233 firms across 22 emerging markets to analyze how credit constraints and low-quality firm management inhibit corporate investment in green technologies. For identification we exploit quasi-exogenous variation in local credit conditions and in exposure to weather shocks. Our results suggest that both financial frictions and managerial constraints slow down firm investment in more energy efficient and less polluting technologies. Complementary analysis of data from the European Pollutant Release and Transfer Register (E-PRTR) corroborates some of this evidence by revealing that in areas where banks deleveraged more after the global financial crisis, industrial facilities reduced their carbon emissions by less. On aggregate this kept local emissions 15% above the level they would have been in the absence of financial frictions.
URN:NBN:fi:bof-202105171236
Keywords: D22; L23; G32; L20; Q52; Q53; 330; Financial frictions; management practices; CO2 emissions; energy efficiency